2007
DOI: 10.1021/jp075391j
|View full text |Cite
|
Sign up to set email alerts
|

Nonresonant Background Suppression in Broadband Vibrational Sum-Frequency Generation Spectroscopy

Abstract: Suppression of the nonresonant background in vibrational sum-frequency generation (SFG) in the broadband multiplex configuration is achieved using a time-asymmetric pulse, created by passing a femtosecond pulse through a Fabry-Perot e ´talon, to temporally discriminate between the faster nonresonant and slower resonant contributions. A mixed time and frequency domain explanation of the SFG process is presented, and spectra with high time resolutions and high degrees of nonresonant background suppression are ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
248
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 185 publications
(255 citation statements)
references
References 18 publications
6
248
1
Order By: Relevance
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 8 suppress the nonresonant response of the silicon substrate. [42][43][47][48] The PPP spectrum showed three resonant vibrational modes of the terminal -CH 3 group, which are assignable to the symmetric C-H stretch (r + ) at ~2865 cm -1 , the asymmetric C-H stretch (r -) at ~2962 cm -1 , and the Fermi resonance ( ) of the r + mode with the C-H asymmetric bending overtone, at ~2933 cm -1 . 24,42,[49][50][51] The SSP spectrum, which exhibited a significant reduction in signal intensity compared with the PPP spectrum, only showed signatures ascribable to the symmetric C-H stretch (r + ) at ~2863 cm -1 and the Fermi resonance ( ) at ~2935 cm -1 .…”
Section: Acs Paragon Plus Environmentmentioning
confidence: 99%
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 8 suppress the nonresonant response of the silicon substrate. [42][43][47][48] The PPP spectrum showed three resonant vibrational modes of the terminal -CH 3 group, which are assignable to the symmetric C-H stretch (r + ) at ~2865 cm -1 , the asymmetric C-H stretch (r -) at ~2962 cm -1 , and the Fermi resonance ( ) of the r + mode with the C-H asymmetric bending overtone, at ~2933 cm -1 . 24,42,[49][50][51] The SSP spectrum, which exhibited a significant reduction in signal intensity compared with the PPP spectrum, only showed signatures ascribable to the symmetric C-H stretch (r + ) at ~2863 cm -1 and the Fermi resonance ( ) at ~2935 cm -1 .…”
Section: Acs Paragon Plus Environmentmentioning
confidence: 99%
“…Due to this, vibrational bands in a SFG spectrum can be broad, asymmetric and frequency-shifted with respect to the molecular response. NRB suppression can be achieved by introducing a time-delay between the fs IR and the ps visible pulses, as demonstrated for the case of time-asymmetric pulses from an étalon [9]. We note, however, that applying a time delay in this case may exclude the initial part of the FID, potentially leading to broad vibrational peaks in the observed SFG spectrum.…”
Section: Introductionmentioning
confidence: 84%
“…1(b). A general time-asymmetric scheme is based on the use of air-spaced Fabry-Perot étalons [8][9][10]. If the étalon air-gap d is chosen to be less than the coherence length l c of the pulse, the transmitted pulse has a smooth time-asymmetric shape, appearing in form as an exponential decay with decay constant equal to the photon cavity lifetime, as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Lagutchev et al reported that the nonresonant background signal from the gold substrate in broadband SFG measurements can be significantly reduced by introducing a time delay between the IR and visible pulses. 8 When the per-deuterated dielectric thin film is replaced by a per-protonated one, the resonance signal will come from both interfaces, in which case the model is modified by including the contribution of the resonant C-H signal from the buried interface ͑see below͒. No resonant SFG signal will be generated from the bulk of this multilayer film due to its centrosymmetric structure.…”
Section: Methodsmentioning
confidence: 99%